Hepatic lipid accumulation alters global histone h3 lysine 9 and 4 trimethylation in the peroxisome proliferator-activated receptor alpha network. - Hee-Jin Jun; Jinyoung Kim; Minh-Hien Hoang; Sung-Joon Lee (PLoS ONE, 2012)
Recent data suggest that the etiology of several metabolic diseases is closely associated with transcriptome alteration by aberrant histone methylation. We performed DNA microarray and ChIP-on-chip analyses to examine transcriptome profiling and trimethylation alterations to identify the genomic signature of nonalcoholic fatty liver disease (NAFLD), the most common form of chronic liver disease. Transcriptome analysis showed that steatotic livers in high-fat diet-fed apolipoprotein E2 mice significantly altered the expression of approximately 70% of total genes compared with normal diet-fed control livers, suggesting that hepatic lipid accumulation induces dramatic alterations in gene expression in vivo. Also, pathway analysis suggested that genes encoding chromatin-remodeling enzymes, such as jumonji C-domain-containing histone demethylases that regulate histone H3K9 and H3K4 trimethylation (H3K9me3, H3K4me3), were significantly altered in steatotic livers. Thus, we further investigated the global H3K9me3 and H3K4me3 status in lipid-accumulated mouse primary hepatocytes by ChIP-on-chip analysis. Results showed that hepatic lipid accumulation induced aberrant H3K9me3 and H3K4me3 status in peroxisome proliferator-activated receptor alpha and hepatic lipid catabolism network genes, reducing their mRNA expression compared with non-treated control hepatocytes. This study provides the first evidence that epigenetic regulation by H3K9me3 and H3K4me3 in hepatocytes may be involved in hepatic steatosis and the pathogenesis of NAFLD. Thus, control of H3K9me3 and H3K4me3 represents a potential novel NAFLD prevention and treatment strategy.